The transformational leader and the routine leader: their manifestations in men and women - Fabregas Rodado, Carlos J.; Fabregas Rodado, Carlos J. (Corporación Universitaria Americana, 2020)
This theory reflection is based on Bass's (2008) studies on transformational leadership. In this approach, transformational leadership is generally defined in terms of the leader's behavior and the effect on followers. From Bass's reflection, it is considered as analysis variables to identify leadership effectiveness. In light of this approach, differences are shown in the theoretical thoughts of Yulk (1989) Kotter (2009) and others who evaluate the effectiveness of leadership in terms of the consequences of the leader's actions for followers and participants of the organization. From a labor context, the role of the transformational leader in organizations is analyzed, taking into account actions such as the participation of the manager. In this sense, reference is made to the routine manager, the change in organizations, the role of women as leaders of change and transformation, and the ethical consideración that transformations imply. The theoretical contributions of Bass (2008), Kotter (2009), Yulk, (1989) Robbins & Coulter (2006), Torres (2009) Mintzberg (1973) have been taken into account. For the validation of reflective analysis the technique used is the problem question, concluding that it can be affirmed that transformational leadership in organizations is subject to the results that it can generate, based on the references cited.